Attitude to and Usage Intention of High School Students Toward Electric Two-Wheeled Vehicles in Hanoi City - Trinh, Thu Thuy (H. : ĐHQGHN, 2019)
In recent years, electric two-wheeled vehicles (E2Ws) including electric bicycles and electric motorcycles have been used widely in Vietnam. Currently, the total number of E2Ws used is 3 million and with an average growth rate of 13.33% an estimated 6 million E2Ws will be used in 2024. E2Ws have been used widely among Vietnam’s youth. Based on the Theory of Planned Behavior (TPB) of Ajzen (2005, 2016) [1, 2], the main purpose of this research is to identify factors affecting the attitude to and intention of high school students in Hanoi city towards E2W usage and their affected level. The analytical results show that the attitude towards E2W usage is influenced respectively in descending order by (i) perceptions of economic benefit, (ii) usage convenience, (iii) friendly environmental awareness, (iv) stylish design. Usage intention towards E2Ws is determined respectively in descending order by (i) subjective norm, (ii) attitude toward E2W usage, (iii) the attraction of motorcycles. Based on the research results, some proposals for producers, authorities and policy-makers have been recommended